Faktor Kepuasan Kerja Karyawan Outsourcing Terhadap Kinerja - Anisya, Fatimah Nur; Utari, Ayu (Lembaga Publikasi Ilmiah Nusantara, 2023)
This study aims to identify the factors of job satisfaction among outsourced employees at PT Catur Daya Sukses and to analyze their influence on employee performance. The research focuses on job satisfaction and performance variables to examine the determinants of employee job satisfaction and how these factors affect work performance. A quantitative research approach was employed by distributing structured questionnaires to 10 outsourced employees from different divisions within the company. Data collection was conducted directly by providing respondents with a list of questions designed to measure levels of job satisfaction and performance. The collected data were then analyzed using factor analysis to identify the dominant factors influencing job satisfaction. The results indicate that job satisfaction factors play a significant role and are the main determinants affecting the performance of outsourced employees. These findings suggest that improving job satisfaction can contribute positively to enhancing employee performance at PT Catur Daya Sukses.